Temperature-resistant and tear-resistant PET composite material and preparation method thereof

CN122978660APending Publication Date: 2026-10-27JIANGXI MICRO CROWN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611130600.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但无机填料大幅降低熔体流动性和制品表面质量,增加了加工难度;而直接与高黏度耐热聚合物共混常因相容性差、分散不均,导致熔体黏度进一步升高,成型困难

Benefits of technology

[0015]有益效果是:1、本发明以2,2’,7,7’-四溴-9,9’-螺二芴为起始物,通过Miyaura硼化、氧化水解和羟乙基化三步化学反应,构筑了四(2-羟乙氧基)螺二芴这一高刚性、四官能度的芳香族起始剂,随后与对苯二甲酸二甲酯、乙二醇和聚乙二醇单甲醚原位缩聚,得到以螺二芴为核、PET-co-PEG为臂的四臂共聚酯。利用螺二芴核心极高的热稳定性和刚性的三维立体构型,在PET熔体中作为刚性异质表面,通过降低成核自由能垒来诱导PET在其表面快速有序地结晶,显著提高结晶温度和结晶度,从而有效提高复合材料的强度和热变形温度,而其具备的拓扑结构赋予该助剂独特的大体积,配合臂上聚乙二醇链段,在熔融加工剪切场下,四臂分子类似“分子滚珠”,极大地削弱了PET线形链间的物理缠结,使体系的粘度明显下降,从而赋予PET复合材料良好的流动加工性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of polymer composites, and particularly relates to a temperature-resistant and tear-resistant PET composite material and a preparation method thereof. The application comprises the following steps: preparation of temperature-resistant flow-promoting particles; preparation of tear-resistant reinforcing agents; and extrusion granulation of the PET composite material. The application uses 2,2',7,7'-tetrabromo-9,9'-spirobifluorene as a starting material, constructs a high-rigidity and four-function aromatic starting agent of tetra(2-hydroxyethoxy)spirobifluorene through three-step chemical reactions of Miyaura boronation, oxidative hydrolysis and hydroxyethylation, and then in-situ polycondensates the starting agent with dimethyl terephthalate, ethylene glycol and polyethylene glycol monomethyl ether to obtain a four-arm copolyester with spirobifluorene as a core and PET-co-PEG as arms, which can effectively improve the heat distortion temperature of the composite material and endow the composite material with good flow processing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer composite materials technology, specifically relating to a temperature-resistant and tear-resistant PET composite material and its preparation method. Background Technology

[0002] Polyethylene terephthalate (PET) is widely used in fibers, bottle flakes, films, and engineering plastics due to its excellent mechanical properties, electrical insulation, and chemical stability. However, PET has inherent defects such as slow crystallization rate, low heat distortion temperature, and poor tear resistance, which severely limit its application in food packaging and protective fabrics.

[0003] To improve the temperature resistance of PET, existing processes typically add inorganic fillers such as glass fiber and nano-montmorillonite, or blend it with heat-resistant polymers such as polycarbonate and polyphenylene ether. However, inorganic fillers significantly reduce melt flowability and product surface quality, increasing processing difficulty. Direct blending with high-viscosity heat-resistant polymers often results in poor compatibility and uneven dispersion, leading to further increases in melt viscosity and molding difficulties. Meanwhile, PET's poor tear resistance is also a key bottleneck limiting its application. Industrially, elastomers (such as POE-g-GMA, core-shell rubber) or polyolefin ionomers are commonly used for reinforcement and toughening. However, while the introduction of elastomers can significantly improve tear resistance, it often comes at the cost of sacrificing the material's heat distortion temperature, making it difficult to balance heat resistance and tear resistance. Furthermore, some existing technologies improve PET strength by adding fibrous fillers or rigid particles, but these methods usually offer limited improvement in tear resistance and easily cause stress concentration, which weakens the material's resistance to crack propagation. Summary of the Invention

[0004] To address the aforementioned technical deficiencies, this invention presents a temperature-resistant and tear-resistant PET composite material and its preparation method. The prepared PET composite material possesses excellent temperature resistance, superior processing fluidity, and high-strength tear resistance.

[0005] A method for preparing a temperature-resistant and tear-resistant PET composite material includes the following steps: S1: Preparation of temperature-resistant flow-promoting particles Under nitrogen protection, 2,2',7,7'-tetrabromo-9,9'-spirobifluorene, pinacol diborate, anhydrous potassium acetate, and Pd catalyst were reacted in anhydrous 1,4-dioxane. After dilution and filtration, the filtrate was washed and dried, then the solvent was removed by rotary evaporation and purified by chromatography to obtain pinacol diborate-spirobifluorene. The spirobifluorene-spirobifluorene-spirobifluorene was then oxidized using a hydrogen peroxide and sodium hydroxide system to prepare tetrahydroxybenzene. Benzyl phenyl-spirodifluorene was mixed with anhydrous potassium carbonate and 2-chloroethanol and reacted at elevated temperature to prepare tetra(2-hydroxyethoxy)spirodifluorene. Dimethyl terephthalate, ethylene glycol, polyethylene glycol monomethyl ether and tetra(2-hydroxyethoxy)spirodifluorene were mixed and reacted under the catalysis of tetrabutyl titanate until no methanol was generated. Then, polycondensation was carried out under the action of antimony trioxide and triphenyl phosphite to prepare copolyester for granulation to obtain temperature-resistant flow-promoting particles. S2: Preparation of tear-resistant reinforcing agent Cucurbita[7]urea and di-terminated alkynyl polyethylene glycol were placed in deionized water and stirred. After being kept at low temperature overnight, the precipitate was collected and freeze-dried to obtain quasi-polyrotaxane. Quasi-polyrotaxane was added to a mixed solution of N,N-dimethylformamide and deionized water, and then 1-azadiazonane, copper sulfate pentahydrate and sodium ascorbate were added. The mixture was heated and reacted under nitrogen protection. The resulting mixed slurry was dialyzed in deionized water and freeze-dried to obtain cucurbita polyrotaxane. Sodium p-hydroxybenzoate, cucurbita polyrotaxane and dimethyl sulfoxide solution were mixed and stirred, and the solvent was removed by rotary evaporation under reduced pressure to obtain tear-resistant reinforcing agent. S3: Extrusion granulation of PET composite materials PET masterbatch is dried to obtain dried PET masterbatch. 100 parts by weight of dried PET masterbatch, 5-12 parts by weight of heat-resistant flow-promoting particles, 3-5 parts by weight of tear-resistant reinforcing agent, 0.2-0.5 parts by weight of antioxidant and 0.2-0.5 parts by weight of calcium stearate are mixed evenly and then placed in a twin-screw extruder for extrusion granulation to obtain PET composite material.

[0006] Furthermore, the preparation of the temperature-resistant flow-promoting particles in step S1 specifically includes the following steps: S1.1: Under nitrogen protection, add 6-7 parts by weight of 2,2',7,7'-tetrabromo-9,9'-spirobifluorene, 12-15 parts by weight of pinacol diborate, 15-17 parts by weight of anhydrous potassium acetate, and 0.4-0.6 parts by weight of Pd catalyst to a container, then add 500-600 parts by weight of anhydrous 1,4-dioxane, stir at 200-250 rpm for 25-30 min, and then heat to 90-95℃ to react for 24-25 h to obtain... Add 550-600 parts by weight of ethyl acetate to the reaction solution and let it cool to room temperature. Stir and dilute. Then filter with diatomaceous earth. Collect the filtrate and add 100-120 parts by weight of saturated brine. Stir until homogeneous. Centrifuge and collect the separated organic phases. Add 6-8 wt% of anhydrous magnesium sulfate and stir to dry. Filter and collect the filtrate. Remove the solvent by rotary evaporation under reduced pressure to obtain the crude product. Purify the crude product by silica gel column chromatography to obtain pennatol tetraborate-spirodifluorene. S1.2: Dissolve 8-10 parts by weight of pinacol tetraborate-spirobifluorene in 80-100 parts by weight of tetrahydrofuran, cool to 4-5°C in an ice-water bath, then add 12-15 parts by weight of hydrogen peroxide aqueous solution and 15-20 parts by weight of sodium hydroxide aqueous solution in sequence, transfer to room temperature and stir for 4-5 hours, add saturated sodium sulfite solution to quench the reaction, then extract with 80-100 parts by weight of ethyl acetate 2-3 times, combine the organic phases, add 25-30 parts by weight of saturated brine and stir to wash, centrifuge to collect the organic phase, add 6-8 wt% of anhydrous magnesium sulfate and stir to dry, filter and collect the filtrate, remove the solvent by rotary evaporation under reduced pressure, collect the crude reaction product and recrystallize with excess dichloromethane / n-hexane mixed solvent to obtain tetrahydroxyphenyl-spirobifluorene; S1.3: Under a nitrogen atmosphere, 10-12 parts by weight of tetrahydroxyphenyl-spirobifluorene were dissolved in 150-200 parts by weight of anhydrous N,N-dimethylformamide, 33-35 parts by weight of anhydrous potassium carbonate and 25-27 parts by weight of 2-chloroethanol were added, the mixture was heated to 115-120℃ and stirred for 24 h, cooled and filtered, the filtrate was collected and poured into 8-10 times its volume of 3-4℃ ice water to precipitate the precipitate, and dried in a 60℃ oven for 3-4 h to obtain tetra(2-hydroxyethoxy)spirobifluorene; S1.4: Add 77-80 parts by weight of dimethyl terephthalate, 44-48 parts by weight of ethylene glycol, 60-65 parts by weight of polyethylene glycol monomethyl ether, and 14-16 parts by weight of tetra(2-hydroxyethoxy)spirobifluorene to a container, then add 0.1-0.15 parts by weight of tetrabutyl titanate. Heat to 190-200℃ under nitrogen purging, stir for 3-3.5 hours, and distill off the byproduct methanol. When no more methanol distills off, add... Add 0.05-0.06 parts by weight of antimony trioxide and 0.6-0.8 parts by weight of triphenyl phosphite, and carry out a polycondensation reaction for 2-2.5 hours at 275-280℃ and 60-80Pa to obtain a copolyester. Then, purge with nitrogen to restore the pressure to normal. Transfer the copolyester to an extruder for granulation, control the particle size to 3-5 mm, and then place it under vacuum drying at 120-125℃ to obtain heat-resistant flow-promoting granules.

[0007] Furthermore, the preparation of the tear-resistant reinforcing agent in step S2 specifically includes the following steps: S2.1: Add 6-8 parts by weight of cucurbit[7]urea and 1.5-2 parts by weight of di-terminated alkynyl polyethylene glycol to 25-30 parts by weight of deionized water, stir for 24-25 hours at 40-60℃ and 200-300 rpm, then place in a 4℃ refrigerator overnight, filter and collect the precipitate for freeze drying to obtain quasi-polyrotaxane; S2.2: Add the quasi-polyrotaxane obtained in step S2.1 to 100-120 parts by weight of a mixed solution prepared by N,N-dimethylformamide and deionized water in a volume ratio of 1:1, then add 0.8-1 parts by weight of 1-adamantane, 0.02-0.03 parts by weight of copper sulfate pentahydrate and 0.07-0.08 parts by weight of sodium ascorbate, and then heat to 40-42℃ under nitrogen protection and stir for 40-48 hours to obtain a mixed slurry; S2.3: Transfer the mixed slurry to a dialysis bag with a molecular weight cutoff of 10,000, dialyze in deionized water for 4-5 days, changing the deionized water every 8 hours, and then freeze-dry the mixed slurry in the dialysis bag to obtain cucurbita polyrotaxane. S2.4: At room temperature, sodium p-hydroxybenzoate, cucurbita polyrotaxane and dimethyl sulfoxide solution are added to a container in a mass ratio of 1:(5-7):(20-25), and then stirred at a stirring speed of 250-300 rpm for 6-8 hours. The dimethyl sulfoxide solution is removed by rotary evaporation under reduced pressure to obtain the tear-resistant reinforcing agent.

[0008] Furthermore, the extrusion granulation of the PET composite material in step S3 specifically includes the following steps: S3.1: Dry PET masterbatch with an intrinsic viscosity of 0.8-0.85 in a forced-air drying oven at 85-90℃ for 5-6 hours to obtain dried PET masterbatch. Mix 100 parts by weight of dried PET masterbatch, 5-12 parts by weight of heat-resistant flow-promoting particles, 3-5 parts by weight of tear-resistant reinforcing agent, 0.2-0.5 parts by weight of antioxidant and 0.2-0.5 parts by weight of calcium stearate evenly to obtain a premix. S3.2: The premixed material is fed into a twin-screw extruder for extrusion granulation. The temperatures of each zone of the twin-screw extruder are as follows: Zone 1 200-205℃, Zone 2 215-220℃, Zone 3 225-235℃, Zone 4 240-250℃, Zone 5 255-260℃, Zone 6 260-265℃, Zone 7 265-270℃, and the die temperature is 265-270℃. The screw length-to-diameter ratio is (32-35):1, the screw speed is 250-300 rpm, and the particle size is controlled at 3 mm to obtain PET composite material.

[0009] Furthermore, the Pd catalyst in step S1.1 is 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride.

[0010] Further, in step S1.1, the eluent for silica gel column chromatography is prepared by mixing petroleum ether and ethyl acetate in a volume ratio of 4:1.

[0011] Furthermore, in step S1.2, the mass concentration of the hydrogen peroxide aqueous solution is 30-32%, and the mass concentration of the sodium hydroxide aqueous solution is 7-8%.

[0012] Furthermore, in step S2.1, the polyethylene glycol in the di-terminated alkynyl polyethylene glycol has a molecular weight of 20,000-35,000.

[0013] Further, the antioxidant in step S3.1 is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:(0.5-0.6).

[0014] A temperature-resistant and tear-resistant PET composite material is prepared by the above-mentioned method for preparing a temperature-resistant and tear-resistant PET composite material.

[0015] The beneficial effects are as follows: 1. This invention uses 2,2',7,7'-tetrabromo-9,9'-spirodifluorene as a starting material and constructs tetra(2-hydroxyethoxy)spirodifluorene, a highly rigid, tetrafunctional aromatic initiator, through a three-step chemical reaction of Miyaura boration, oxidative hydrolysis and hydroxyethylation. Subsequently, it undergoes in-situ polycondensation with dimethyl terephthalate, ethylene glycol and polyethylene glycol monomethyl ether to obtain a four-arm copolyester with spirodifluorene as the core and PET-co-PEG as the arms. By utilizing the extremely high thermal stability and rigid three-dimensional structure of the spirodifluorene core, it acts as a rigid heterogeneous surface in PET melt. By lowering the nucleation free energy barrier, it induces rapid and orderly crystallization of PET on its surface, significantly increasing the crystallization temperature and crystallinity. This effectively improves the strength and heat distortion temperature of the composite material. Its unique topological structure endows the additive with a large volume. Combined with the polyethylene glycol segments on the arms, under the melt processing shear field, the four-arm molecules resemble "molecular balls," greatly weakening the physical entanglement between the linear chains of PET. This significantly reduces the viscosity of the system, thus giving the PET composite material excellent flow processing properties.

[0016] 2. In this invention, a quasi-polyrotaxane is formed by host-guest recognition assembly of di-terminated alkyne polyethylene glycol and cucurbit[7]urea. Then, 1-azidoadaramane is used as the end-capping group to efficiently generate thermally stable cucurbiturea polyrotaxane in copper-catalyzed azido-alkyne cycloaddition reaction (CuAAC). Finally, a tear-resistant reinforcing agent is obtained by physically loading the organic nucleating agent sodium p-hydroxybenzoate. Sodium p-hydroxybenzoate, as an aromatic carboxylic acid sodium salt, has strong nucleation activity. During the cooling process of PET melt, sodium p-hydroxybenzoate molecules loaded on the surface of polyrotaxane can induce PET chain segments to arrange in an orderly manner around the particles, forming a dense and oriented crystalline interface layer, inducing PET to crystallize rapidly, improving its crystallinity and heat distortion temperature. When the composite material is torn or stretched externally, the "pulley effect" of cucurbita polyrotaxane and the nucleation crystal layer produce a dynamic synergistic effect: the dense interface crystal layer acts as a rigid skeleton, concentrating and guiding the external force to the polyrotaxane core. At this time, the cucurbita macrocycles [7] that can slide freely on the long axis of polyethylene glycol dissipate a large amount of external energy through the synergistic sliding motion along the axis, preventing microcracks from expanding into penetrating tears. Therefore, loading sodium p-hydroxybenzoate onto polyrotaxane can also synergistically improve the strength of PET composite materials. Detailed Implementation

[0017] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] Example 1 A method for preparing a temperature-resistant and tear-resistant PET composite material specifically includes the following steps: S1: Preparation of temperature-resistant flow-promoting particles S1.1: Under nitrogen protection, add 6 parts by weight of 2,2',7,7'-tetrabromo-9,9'-spirodifluorene, 12 parts by weight of pinacol diborate, 15 parts by weight of anhydrous potassium acetate, and 0.4 parts by weight of 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride to a container, then add 500 parts by weight of anhydrous 1,4-dioxane, stir at 200 rpm for 25 min, and then heat to 90°C for 24 h to obtain a reaction solution. After the reaction solution cools to room temperature, add 550... Ethyl acetate was diluted by stirring, then filtered through diatomaceous earth. The filtrate was collected and 100 parts by weight of saturated brine was added and stirred until homogeneous. The mixture was then centrifuged, and the separated organic phases were collected. 6 wt% anhydrous magnesium sulfate was added and the mixture was dried by stirring. The filtrate was collected and the solvent was removed by rotary evaporation under reduced pressure to obtain the crude product. The crude product was purified by silica gel column chromatography. The eluent for the silica gel column chromatography was prepared by mixing petroleum ether and ethyl acetate in a volume ratio of 4:1 to obtain pennatol tetraborate-spirodifluorene. S1.2: Dissolve 8 parts by weight of pennatol tetraborate-spirobifluorene in 80 parts by weight of tetrahydrofuran, cool to 4°C in an ice-water bath, then add 12 parts by weight of hydrogen peroxide aqueous solution and 15 parts by weight of sodium hydroxide aqueous solution in sequence, wherein the mass concentration of hydrogen peroxide aqueous solution is 30% and the mass concentration of sodium hydroxide aqueous solution is 7%, transfer to room temperature and stir for 4 hours, add saturated sodium sulfite solution to quench the reaction, then extract twice with 80 parts by weight of ethyl acetate, combine the organic phases, add 25 parts by weight of saturated brine and stir to wash, centrifuge to collect the organic phase, add 6 wt% anhydrous magnesium sulfate and stir to dry, filter and collect the filtrate, remove the solvent by rotary evaporation under reduced pressure, collect the crude reaction product and recrystallize it with excess dichloromethane / n-hexane mixed solvent to obtain tetrahydroxyphenyl-spirobifluorene; S1.3: Under a nitrogen atmosphere, 10 parts by weight of tetrahydroxyphenyl-spirobifluorene were dissolved in 150 parts by weight of anhydrous N,N-dimethylformamide, 33 parts by weight of anhydrous potassium carbonate and 25 parts by weight of 2-chloroethanol were added, the mixture was heated to 115°C and stirred for 24 h, cooled and filtered, the filtrate was collected and poured into 8 times its volume of 3°C ice water to precipitate the precipitate, and dried in a 60°C oven for 3 h to obtain tetra(2-hydroxyethoxy)spirobifluorene; S1.4: 77 parts by weight of dimethyl terephthalate, 44 parts by weight of ethylene glycol, 60 parts by weight of polyethylene glycol monomethyl ether, and 14 parts by weight of tetra(2-hydroxyethoxy)spirobifluorene were added to a container, followed by 0.1 parts by weight of tetrabutyl titanate. The mixture was heated to 190°C under nitrogen purging and stirred for 3 hours. The byproduct methanol was distilled off. When no more methanol was distilled off, 0.05 parts by weight of antimony trioxide and 0.6 parts by weight of triphenyl phosphite were added. Polycondensation reaction was carried out at 275°C and 60 Pa for 2 hours to obtain a copolyester. Nitrogen gas was introduced to restore the pressure to normal. The copolyester was transferred to an extruder for granulation, and the particle size was controlled to be 3 mm. Then, it was placed at 120°C for vacuum drying to obtain heat-resistant flow-promoting granules.

[0019] S2: Preparation of tear-resistant reinforcing agent S2.1: Add 6 parts by weight of cucurbit[7]urea and 1.5 parts by weight of di-terminated alkynyl polyethylene glycol to 25 parts by weight of deionized water. The molecular weight of polyethylene glycol in the di-terminated alkynyl polyethylene glycol is 20,000. Stir for 24 hours at 40°C and 200 rpm, then place in a 4°C refrigerator overnight. Filter and collect the precipitate for freeze drying to obtain quasi-polyrotaxane. S2.2: Add the quasi-polyrotaxane obtained in step S2.1 to 100 parts by weight of a mixed solution prepared by N,N-dimethylformamide and deionized water in a volume ratio of 1:1, then add 0.8 parts by weight of 1-adamantane, 0.02 parts by weight of copper sulfate pentahydrate and 0.07 parts by weight of sodium ascorbate, and then heat to 40°C under nitrogen protection and stir for 40 hours to obtain a mixed slurry; S2.3: The mixed slurry was transferred to a dialysis bag with a molecular weight cutoff of 10,000 and dialyzed in deionized water for 4 days, with the deionized water being changed every 8 hours. Then the mixed slurry in the dialysis bag was freeze-dried to obtain cucurbita polyrotaxane. S2.4: At room temperature, sodium p-hydroxybenzoate, cucurbita polyrotaxane and dimethyl sulfoxide solution were added to a container in a mass ratio of 1:5:20, and then stirred at 250 rpm for 6 h. The dimethyl sulfoxide solution was removed by rotary evaporation under reduced pressure to obtain the tear-resistant reinforcing agent.

[0020] S3: Extrusion granulation of PET composite materials S3.1: Dry PET masterbatch with intrinsic viscosity of 0.8 in an 85℃ forced-air drying oven for 5 hours to obtain dried PET masterbatch. Mix 100 parts by weight of dried PET masterbatch, 5 parts by weight of heat-resistant flow-promoting particles, 3 parts by weight of tear-resistant reinforcing agent, 0.2 parts by weight of antioxidant and 0.2 parts by weight of calcium stearate evenly. The antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.5 to obtain a premix. S3.2: The premixed material is fed into a twin-screw extruder for extrusion granulation. The temperatures of each zone of the twin-screw extruder are as follows: Zone 1 200℃, Zone 2 215℃, Zone 3 225℃, Zone 4 240℃, Zone 5 255℃, Zone 6 260℃, Zone 7 265℃, and the die temperature is 265℃. The screw length-to-diameter ratio is 32:1, the screw speed is 250 rpm, and the particle size is controlled at 3 mm to obtain PET composite material.

[0021] Example 2 A method for preparing a temperature-resistant and tear-resistant PET composite material specifically includes the following steps: S1: Preparation of temperature-resistant flow-promoting particles S1.1: Under nitrogen protection, add 6.5 parts by weight of 2,2',7,7'-tetrabromo-9,9'-spirobifluorene, 13 parts by weight of pinacol diborate, 16 parts by weight of anhydrous potassium acetate, and 0.5 parts by weight of 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride to a container, then add 550 parts by weight of anhydrous 1,4-dioxane. Stir at 200 rpm for 30 min, then heat to 95°C and react for 24 h to obtain a reaction solution. After the reaction solution cools to room temperature, add 55... 0 parts by weight of ethyl acetate were stirred and diluted, then filtered through diatomaceous earth. The filtrate was collected and 110 parts by weight of saturated brine was added and stirred evenly. Then, the mixture was centrifuged and the separated organic phases were collected. 7 wt% of anhydrous magnesium sulfate was added and stirred to dry the mixture. The filtrate was collected and the solvent was removed by rotary evaporation under reduced pressure to obtain the crude product. The crude product was purified by silica gel column chromatography. The eluent for silica gel column chromatography was prepared by mixing petroleum ether and ethyl acetate in a volume ratio of 4:1 to obtain pennaol tetraborate-spirodifluorene. S1.2: 9 parts by weight of pinacol tetraborate-spirobifluorene were dissolved in 90 parts by weight of tetrahydrofuran and cooled to 5°C in an ice-water bath. Then, 12 parts by weight of hydrogen peroxide aqueous solution and 20 parts by weight of sodium hydroxide aqueous solution were added sequentially. The mass concentration of the hydrogen peroxide aqueous solution was 32% and the mass concentration of the sodium hydroxide aqueous solution was 7%. The mixture was stirred at room temperature for 5 hours. The reaction was quenched by adding saturated sodium sulfite solution. The mixture was then extracted three times with 90 parts by weight of ethyl acetate. The organic phases were combined and washed with 25 parts by weight of saturated brine. The organic phase was collected by centrifugation and dried with 7 wt% anhydrous magnesium sulfate. The filtrate was collected and the solvent was removed by rotary evaporation under reduced pressure. The crude product was collected and recrystallized using an excess of dichloromethane / n-hexane mixed solvent to obtain tetrahydroxyphenyl-spirobifluorene. S1.3: Under a nitrogen atmosphere, 11 parts by weight of tetrahydroxyphenyl-spirobifluorene were dissolved in 180 parts by weight of anhydrous N,N-dimethylformamide, 34 parts by weight of anhydrous potassium carbonate and 26 parts by weight of 2-chloroethanol were added, the mixture was heated to 120°C and stirred for 24 h, cooled and filtered, the filtrate was collected and poured into 10 times its volume of 3°C ice water to precipitate the precipitate, and dried in a 60°C oven for 4 h to obtain tetra(2-hydroxyethoxy)spirobifluorene; S1.4: 78 parts by weight of dimethyl terephthalate, 46 parts by weight of ethylene glycol, 63 parts by weight of polyethylene glycol monomethyl ether, and 15 parts by weight of tetra(2-hydroxyethoxy)spirobifluorene were added to a container, followed by 0.12 parts by weight of tetrabutyl titanate. The mixture was heated to 200°C under nitrogen purging and stirred for 3 hours. The byproduct methanol was distilled off. When no more methanol was distilled off, 0.06 parts by weight of antimony trioxide and 0.6 parts by weight of triphenyl phosphite were added. Polycondensation was carried out at 280°C and 60 Pa for 2.5 hours to obtain a copolyester. Nitrogen gas was introduced to restore the pressure to normal. The copolyester was transferred to an extruder for granulation, with the particle size controlled at 4 mm. The granules were then vacuum dried at 125°C to obtain heat-resistant flow-promoting granules.

[0022] S2: Preparation of tear-resistant reinforcing agent S2.1: Add 7 parts by weight of cucurbit[7]urea and 1.8 parts by weight of di-terminated alkynyl polyethylene glycol to 30 parts by weight of deionized water. The molecular weight of polyethylene glycol in the di-terminated alkynyl polyethylene glycol is 30,000. Stir for 24 hours at 50°C and 250 rpm, then place in a 4°C refrigerator overnight. Filter and collect the precipitate for freeze drying to obtain quasi-polyrotaxane. S2.2: Add the quasi-polyrotaxane obtained in step S2.1 to 110 parts by weight of a mixed solution prepared by N,N-dimethylformamide and deionized water in a volume ratio of 1:1, then add 0.9 parts by weight of 1-adamantane, 0.02 parts by weight of copper sulfate pentahydrate and 0.08 parts by weight of sodium ascorbate, and then heat to 42°C under nitrogen protection and stir for 40 hours to obtain a mixed slurry; S2.3: The mixed slurry was transferred to a dialysis bag with a molecular weight cutoff of 10,000 and dialyzed in deionized water for 4 days, with the deionized water being changed every 8 hours. Then the mixed slurry in the dialysis bag was freeze-dried to obtain cucurbita polyrotaxane. S2.4: At room temperature, sodium p-hydroxybenzoate, cucurbita polyrotaxane and dimethyl sulfoxide solution were added to a container in a mass ratio of 1:6:25, and then stirred at 300 rpm for 6 h. The dimethyl sulfoxide solution was removed by rotary evaporation under reduced pressure to obtain the tear-resistant reinforcing agent.

[0023] S3: Extrusion granulation of PET composite materials S3.1: Dry PET masterbatch with an intrinsic viscosity of 0.85 in a 90℃ forced-air drying oven for 5 hours to obtain dried PET masterbatch. Mix 100 parts by weight of dried PET masterbatch, 8 parts by weight of heat-resistant flow-promoting particles, 4 parts by weight of tear-resistant reinforcing agent, 0.3 parts by weight of antioxidant and 0.4 parts by weight of calcium stearate evenly. The antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.55 to obtain a premix. S3.2: The premixed material is fed into a twin-screw extruder for extrusion granulation. The temperatures of each zone of the twin-screw extruder are as follows: Zone 1 205℃, Zone 2 215℃, Zone 3 235℃, Zone 4 240℃, Zone 5 260℃, Zone 6 260℃, Zone 7 270℃, and the die temperature is 270℃. The screw length-to-diameter ratio is 34:1, the screw speed is 270 rpm, and the particle size is controlled at 3 mm to obtain PET composite material.

[0024] Example 3 A method for preparing a temperature-resistant and tear-resistant PET composite material specifically includes the following steps: S1: Preparation of temperature-resistant flow-promoting particles S1.1: Under nitrogen protection, add 7 parts by weight of 2,2',7,7'-tetrabromo-9,9'-spirodifluorene, 15 parts by weight of pinacol diborate, 17 parts by weight of anhydrous potassium acetate, and 0.6 parts by weight of 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride to a container, then add 600 parts by weight of anhydrous 1,4-dioxane, stir at 250 rpm for 30 min, then heat to 95°C and react for 25 h to obtain a reaction solution. After the reaction solution cools to room temperature, add 600 parts by weight of anhydrous 1,4-dioxane. Ethyl acetate was diluted by stirring, then filtered through diatomaceous earth. The filtrate was collected and 120 parts by weight of saturated brine was added and stirred until homogeneous. The mixture was then centrifuged, and the separated organic phases were collected. 8 wt% anhydrous magnesium sulfate was added and stirred to dry the mixture. The filtrate was collected and the solvent was removed by rotary evaporation under reduced pressure to obtain the crude product. The crude product was purified by silica gel column chromatography. The eluent for the silica gel column chromatography was prepared by mixing petroleum ether and ethyl acetate in a volume ratio of 4:1 to obtain pennatol tetraborate-spirodifluorene. S1.2: 10 parts by weight of pinacol tetraborate-spirobifluorene were dissolved in 100 parts by weight of tetrahydrofuran and cooled to 5°C in an ice-water bath. Then, 15 parts by weight of hydrogen peroxide aqueous solution and 20 parts by weight of sodium hydroxide aqueous solution were added sequentially. The mass concentration of hydrogen peroxide aqueous solution was 32% and the mass concentration of sodium hydroxide aqueous solution was 8%. The mixture was stirred at room temperature for 5 hours. The reaction was quenched by adding saturated sodium sulfite solution. The mixture was then extracted three times with 100 parts by weight of ethyl acetate. The organic phases were combined and washed with 30 parts by weight of saturated brine. The organic phase was collected by centrifugation and dried with 8 wt% anhydrous magnesium sulfate. The filtrate was collected and the solvent was removed by rotary evaporation under reduced pressure. The crude product was collected and recrystallized with an excess of dichloromethane / n-hexane mixed solvent to obtain tetrahydroxyphenyl-spirobifluorene. S1.3: Under a nitrogen atmosphere, 12 parts by weight of tetrahydroxyphenyl-spirobifluorene were dissolved in 200 parts by weight of anhydrous N,N-dimethylformamide, 35 parts by weight of anhydrous potassium carbonate and 27 parts by weight of 2-chloroethanol were added, the mixture was heated to 120°C and stirred for 24 h, cooled and filtered, the filtrate was collected and poured into 10 times its volume of 4°C ice water to precipitate the precipitate, and dried in a 60°C oven for 4 h to obtain tetra(2-hydroxyethoxy)spirobifluorene; S1.4: 80 parts by weight of dimethyl terephthalate, 48 parts by weight of ethylene glycol, 65 parts by weight of polyethylene glycol monomethyl ether, and 16 parts by weight of tetra(2-hydroxyethoxy)spirobifluorene were added to a container, followed by 0.15 parts by weight of tetrabutyl titanate. The mixture was heated to 200°C under nitrogen purging and stirred for 3.5 hours. The byproduct methanol was distilled off. When no more methanol was distilled off, 0.06 parts by weight of antimony trioxide and 0.8 parts by weight of triphenyl phosphite were added. Polycondensation was carried out at 280°C and 80 Pa for 2.5 hours to obtain a copolyester. Nitrogen gas was introduced to restore the pressure to normal. The copolyester was transferred to an extruder for granulation, with the particle size controlled at 5 mm. The granules were then vacuum dried at 125°C to obtain heat-resistant flow-promoting granules.

[0025] S2: Preparation of tear-resistant reinforcing agent S2.1: Add 8 parts by weight of cucurbit[7]urea and 2 parts by weight of di-terminated alkynyl polyethylene glycol to 30 parts by weight of deionized water. The molecular weight of polyethylene glycol in the di-terminated alkynyl polyethylene glycol is 35000. Stir for 25 hours at 60°C and 300 rpm, then place in a 4°C refrigerator overnight. Filter and collect the precipitate for freeze drying to obtain quasi-polyrotaxane. S2.2: Add the quasi-polyrotaxane obtained in step S2.1 to 120 parts by weight of a mixed solution prepared by N,N-dimethylformamide and deionized water in a volume ratio of 1:1, then add 1 part by weight of 1-adamantane, 0.03 parts by weight of copper sulfate pentahydrate and 0.08 parts by weight of sodium ascorbate, and then heat to 42°C under nitrogen protection and stir for 48 hours to obtain a mixed slurry; S2.3: The mixed slurry was transferred to a dialysis bag with a molecular weight cutoff of 10,000 and dialyzed in deionized water for 5 days, with the deionized water being changed every 8 hours. Then the mixed slurry in the dialysis bag was freeze-dried to obtain cucurbita polyrotaxane. S2.4: At room temperature, sodium p-hydroxybenzoate, cucurbita polyrotaxane and dimethyl sulfoxide solution were added to a container in a mass ratio of 1:7:25, and then stirred at 300 rpm for 8 hours. The dimethyl sulfoxide solution was removed by rotary evaporation under reduced pressure to obtain the tear-resistant reinforcing agent.

[0026] S3: Extrusion granulation of PET composite materials S3.1: Dry PET masterbatch with an intrinsic viscosity of 0.85 in a 90℃ forced-air drying oven for 6 hours to obtain dried PET masterbatch. Mix 100 parts by weight of dried PET masterbatch, 12 parts by weight of heat-resistant flow-promoting particles, 5 parts by weight of tear-resistant reinforcing agent, 0.5 parts by weight of antioxidant and 0.5 parts by weight of calcium stearate evenly. The antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.6 to obtain a premix. S3.2: The premixed material is fed into a twin-screw extruder for extrusion granulation. The temperatures of each zone of the twin-screw extruder are as follows: Zone 1 205℃, Zone 2 220℃, Zone 3 235℃, Zone 4 250℃, Zone 5 260℃, Zone 6 265℃, Zone 7 270℃, and the die temperature is 270℃. The screw length-to-diameter ratio is 35:1, the screw speed is 300 rpm, and the particle size is controlled at 3 mm to obtain PET composite material.

[0027] Comparative Example 1: The difference from Example 1 is that steps S1.1-S1.3 are removed in this comparative example, and tetrakis(2-hydroxyethoxy)spirobifluorene is not added in step S1.4. The remaining steps are the same as in Example 1.

[0028] Comparative Example 2: The difference from Example 1 is that the tear-resistant reinforcing agent in step S3.1 is replaced with 0.5 parts by weight of sodium p-hydroxybenzoate, and the remaining steps are the same as in Example 1.

[0029] Comparative Example 3: The difference from Example 1 is that the tear-resistant reinforcing agent in step S3.1 is replaced with 2.5 parts by weight of cucurbita polyrotaxane, and the remaining steps are the same as in Example 1.

[0030] Comparative Example 4: The difference from Example 1 is that the tear-resistant reinforcing agent in step S3.1 is replaced with 0.5 parts by weight of sodium p-hydroxybenzoate and 2.5 parts by weight of cucurbita polyrotaxane, and the remaining steps are the same as in Example 1.

[0031] Sample preparation: The PET composite materials prepared in Examples 1-3 and Comparative Examples 1-4 were injection molded into test samples according to the following standards, and their performance was tested according to the standards: Tensile strength and tear strength tests: The tensile strength of the samples was tested according to the standard GB / T1040.3-2006, and the tear strength of the samples was tested according to the standard GB / T16578.1-2008. Three samples were tested for each group, and the average value was taken. The data is shown in Table 1.

[0032] Flowability test: The spiral length test method was adopted. The injection temperature was set at 270℃. Using a spiral mold, the PET composite materials prepared by Examples 1-3 and Comparative Example 1 were injection molded into spirals at an injection pressure of 100MPa. Three parts of each were injection molded. The spiral length was tested and the average value of each group was calculated. The longer the spiral length, the better the flowability of the composite material.

[0033] Temperature resistance test: The PET composite materials prepared in Examples 1-3 and Comparative Examples 1-4 were injection molded into 250mL plastic bottles, three of each were injection molded, and placed in an environment of 220℃ for 30min for boiling. The appearance changes were detected and the data were recorded as shown in Table 1.

[0034] Table 1: Sample strength and high temperature resistance test results

[0035] As shown in Table 1, the tensile strengths of Examples 1-3 reached 53 MPa, 55 MPa and 57 MPa respectively, the tear strengths reached 231 kN / m, 268 kN / m and 295 kN / m respectively, the helix lengths were 364 mm, 371 mm and 375 mm respectively, and the fluidity was high. After the cooking treatment, the appearance and size of the samples were still not deformed. This proves that the PET composite materials prepared in Examples 1-3 have excellent mechanical strength, tear toughness and temperature resistance.

[0036] Comparative Example 1 removed steps S1.1-S1.3, omitting the tetra(2-hydroxyethoxy)spirodifluorene core and replacing it with a linear PET-co-PEG copolyester as the heat-resistant flow-promoting component. Its tensile strength was only 48 MPa, tear strength decreased to 180 kN / m, helix length was 282 mm, flowability decreased, and severe deformation occurred after cooking. This indicates that the lack of a rigid spirodifluorene core for strong heterogeneous nucleation results in insufficient matrix crystallinity, reduced strength, and inability to effectively resist heat deformation. Simultaneously, the linear copolyester cannot effectively weaken the physical entanglement between PET chains, leading to high melt viscosity, difficulty in molding, and easy deformation after cooking. This demonstrates that only a four-armed copolyester with spirodifluorene as the core and PET-co-PEG as the arms can effectively improve the strength and heat distortion temperature of the composite material while imparting good flow processing properties to the PET composite.

[0037] The data from Comparative Examples 2 and 3 show that both sodium p-hydroxybenzoate and cucurbita polyrotaxane are indispensable for improving the tensile strength and tear resistance of PET composites. However, in Comparative Example 4, which did not combine the two, the strength also decreased. This indicates that only by loading sodium p-hydroxybenzoate onto polyrotaxane can the two work synergistically to improve the strength of PET composites. In contrast, Comparative Example 3, which did not add a nucleating agent, resulted in severe deformation of the plastic bottle. This was because the lack of a nucleating agent reduced the crystallinity of PET, and its heat distortion temperature also decreased.

[0038] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.

Claims

1. A method for preparing a temperature-resistant and tear-resistant PET composite material, characterized in that, Includes the following steps: S1: Preparation of temperature-resistant flow-promoting particles Under nitrogen protection, 2,2',7,7'-tetrabromo-9,9'-spirobifluorene, pinacol diborate, anhydrous potassium acetate, and Pd catalyst were reacted in anhydrous 1,4-dioxane. After dilution and filtration, the filtrate was washed and dried, then the solvent was removed by rotary evaporation and purified by chromatography to obtain pinacol diborate-spirobifluorene. The spirobifluorene-spirobifluorene-spirobifluorene was then oxidized using a hydrogen peroxide and sodium hydroxide system to prepare tetrahydroxybenzene. Benzyl phenyl-spirodifluorene was mixed with anhydrous potassium carbonate and 2-chloroethanol and reacted at elevated temperature to prepare tetra(2-hydroxyethoxy)spirodifluorene. Dimethyl terephthalate, ethylene glycol, polyethylene glycol monomethyl ether and tetra(2-hydroxyethoxy)spirodifluorene were mixed and reacted under the catalysis of tetrabutyl titanate until no methanol was generated. Then, polycondensation was carried out under the action of antimony trioxide and triphenyl phosphite to prepare copolyester for granulation to obtain temperature-resistant flow-promoting particles. S2: Preparation of tear-resistant reinforcing agent Cucurbita[7]urea and di-terminated alkynyl polyethylene glycol were placed in deionized water and stirred. After being kept at low temperature overnight, the precipitate was collected and freeze-dried to obtain quasi-polyrotaxane. Quasi-polyrotaxane was added to a mixed solution of N,N-dimethylformamide and deionized water, and then 1-azadiazonane, copper sulfate pentahydrate and sodium ascorbate were added. The mixture was heated and reacted under nitrogen protection. The resulting mixed slurry was dialyzed in deionized water and freeze-dried to obtain cucurbita polyrotaxane. Sodium p-hydroxybenzoate, cucurbita polyrotaxane and dimethyl sulfoxide solution were mixed and stirred, and the solvent was removed by rotary evaporation under reduced pressure to obtain tear-resistant reinforcing agent. S3: Extrusion granulation of PET composite materials PET masterbatch is dried to obtain dried PET masterbatch. 100 parts by weight of dried PET masterbatch, 5-12 parts by weight of heat-resistant flow-promoting particles, 3-5 parts by weight of tear-resistant reinforcing agent, 0.2-0.5 parts by weight of antioxidant and 0.2-0.5 parts by weight of calcium stearate are mixed evenly and then placed in a twin-screw extruder for extrusion granulation to obtain PET composite material.

2. The method for preparing a temperature-resistant and tear-resistant PET composite material according to claim 1, characterized in that, Step S1, the preparation of temperature-resistant flow-promoting particles, specifically includes the following steps: S1.1: Under nitrogen protection, add 6-7 parts by weight of 2,2',7,7'-tetrabromo-9,9'-spirobifluorene, 12-15 parts by weight of pinacol diborate, 15-17 parts by weight of anhydrous potassium acetate, and 0.4-0.6 parts by weight of Pd catalyst to a container, then add 500-600 parts by weight of anhydrous 1,4-dioxane, stir at 200-250 rpm for 25-30 min, and then heat to 90-95℃ to react for 24-25 h to obtain... Add 550-600 parts by weight of ethyl acetate to the reaction solution and let it cool to room temperature. Stir and dilute. Then filter with diatomaceous earth. Collect the filtrate and add 100-120 parts by weight of saturated brine. Stir until homogeneous. Centrifuge and collect the separated organic phases. Add 6-8 wt% of anhydrous magnesium sulfate and stir to dry. Filter and collect the filtrate. Remove the solvent by rotary evaporation under reduced pressure to obtain the crude product. Purify the crude product by silica gel column chromatography to obtain pennatol tetraborate-spirodifluorene. S1.2: Dissolve 8-10 parts by weight of pinacol tetraborate-spirobifluorene in 80-100 parts by weight of tetrahydrofuran, cool to 4-5°C in an ice-water bath, then add 12-15 parts by weight of hydrogen peroxide aqueous solution and 15-20 parts by weight of sodium hydroxide aqueous solution in sequence, transfer to room temperature and stir for 4-5 hours, add saturated sodium sulfite solution to quench the reaction, then extract with 80-100 parts by weight of ethyl acetate 2-3 times, combine the organic phases, add 25-30 parts by weight of saturated brine and stir to wash, centrifuge to collect the organic phase, add 6-8 wt% of anhydrous magnesium sulfate and stir to dry, filter and collect the filtrate, remove the solvent by rotary evaporation under reduced pressure, collect the crude reaction product and recrystallize with excess dichloromethane / n-hexane mixed solvent to obtain tetrahydroxyphenyl-spirobifluorene; S1.3: Under a nitrogen atmosphere, 10-12 parts by weight of tetrahydroxyphenyl-spirobifluorene were dissolved in 150-200 parts by weight of anhydrous N,N-dimethylformamide, 33-35 parts by weight of anhydrous potassium carbonate and 25-27 parts by weight of 2-chloroethanol were added, the mixture was heated to 115-120℃ and stirred for 24 h, cooled and filtered, the filtrate was collected and poured into 8-10 times its volume of 3-4℃ ice water to precipitate the precipitate, and dried in a 60℃ oven for 3-4 h to obtain tetra(2-hydroxyethoxy)spirobifluorene; S1.4: Add 77-80 parts by weight of dimethyl terephthalate, 44-48 parts by weight of ethylene glycol, 60-65 parts by weight of polyethylene glycol monomethyl ether, and 14-16 parts by weight of tetra(2-hydroxyethoxy)spirobifluorene to a container, then add 0.1-0.15 parts by weight of tetrabutyl titanate. Heat to 190-200℃ under nitrogen purging, stir for 3-3.5 hours, and distill off the byproduct methanol. When no more methanol distills off, add... Add 0.05-0.06 parts by weight of antimony trioxide and 0.6-0.8 parts by weight of triphenyl phosphite, and carry out a polycondensation reaction for 2-2.5 hours at 275-280℃ and 60-80Pa to obtain a copolyester. Then, purge with nitrogen to restore the pressure to normal. Transfer the copolyester to an extruder for granulation, control the particle size to 3-5 mm, and then place it under vacuum drying at 120-125℃ to obtain heat-resistant flow-promoting granules.

3. The method for preparing a temperature-resistant and tear-resistant PET composite material according to claim 1, characterized in that, Step S2, the preparation of the tear-resistant reinforcing agent, specifically includes the following steps: S2.1: Add 6-8 parts by weight of cucurbit[7]urea and 1.5-2 parts by weight of di-terminated alkynyl polyethylene glycol to 25-30 parts by weight of deionized water, stir for 24-25 hours at 40-60℃ and 200-300 rpm, then place in a 4℃ refrigerator overnight, filter and collect the precipitate for freeze drying to obtain quasi-polyrotaxane; S2.2: Add the quasi-polyrotaxane obtained in step S2.1 to 100-120 parts by weight of a mixed solution prepared by N,N-dimethylformamide and deionized water in a volume ratio of 1:1, then add 0.8-1 parts by weight of 1-adamantane, 0.02-0.03 parts by weight of copper sulfate pentahydrate and 0.07-0.08 parts by weight of sodium ascorbate, and then heat to 40-42℃ under nitrogen protection and stir for 40-48 hours to obtain a mixed slurry; S2.3: Transfer the mixed slurry to a dialysis bag with a molecular weight cutoff of 10,000, dialyze in deionized water for 4-5 days, changing the deionized water every 8 hours, and then freeze-dry the mixed slurry in the dialysis bag to obtain cucurbita polyrotaxane. S2.4: At room temperature, sodium p-hydroxybenzoate, cucurbita polyrotaxane and dimethyl sulfoxide solution are added to a container in a mass ratio of 1:(5-7):(20-25), and then stirred at a stirring speed of 250-300 rpm for 6-8 hours. The dimethyl sulfoxide solution is removed by rotary evaporation under reduced pressure to obtain the tear-resistant reinforcing agent.

4. The method for preparing a temperature-resistant and tear-resistant PET composite material according to claim 1, characterized in that, The extrusion granulation of the S3 PET composite material specifically includes the following steps: S3.1: Dry PET masterbatch with an intrinsic viscosity of 0.8-0.85 in a forced-air drying oven at 85-90℃ for 5-6 hours to obtain dried PET masterbatch. Mix 100 parts by weight of dried PET masterbatch, 5-12 parts by weight of heat-resistant flow-promoting particles, 3-5 parts by weight of tear-resistant reinforcing agent, 0.2-0.5 parts by weight of antioxidant and 0.2-0.5 parts by weight of calcium stearate evenly to obtain a premix. S3.2: The premixed material is fed into a twin-screw extruder for extrusion granulation. The temperatures of each zone of the twin-screw extruder are as follows: Zone 1 200-205℃, Zone 2 215-220℃, Zone 3 225-235℃, Zone 4 240-250℃, Zone 5 255-260℃, Zone 6 260-265℃, Zone 7 265-270℃, and the die temperature is 265-270℃. The screw length-to-diameter ratio is (32-35):1, the screw speed is 250-300 rpm, and the particle size is controlled at 3 mm to obtain PET composite material.

5. The method for preparing a temperature-resistant and tear-resistant PET composite material according to claim 2, characterized in that, The Pd catalyst in step S1.1 is 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride.

6. The method for preparing a temperature-resistant and tear-resistant PET composite material according to claim 2, characterized in that, In step S1.1, the eluent for silica gel column chromatography is prepared by mixing petroleum ether and ethyl acetate in a volume ratio of 4:

1.

7. The method for preparing a temperature-resistant and tear-resistant PET composite material according to claim 2, characterized in that, In step S1.2, the mass concentration of the hydrogen peroxide aqueous solution is 30-32%, and the mass concentration of the sodium hydroxide aqueous solution is 7-8%.

8. The method for preparing a temperature-resistant and tear-resistant PET composite material according to claim 3, characterized in that, In step S2.1, the polyethylene glycol in the di-terminated alkynyl polyethylene glycol has a molecular weight of 20,000-35,000.

9. The method for preparing a temperature-resistant and tear-resistant PET composite material according to claim 4, characterized in that, The antioxidant in step S3.1 consists of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:(0.5-0.6).

10. A temperature-resistant and tear-resistant PET composite material, characterized in that, It is prepared by the method of any one of the above claims 1-9 for preparing a heat-resistant and tear-resistant PET composite material.